Vietnamese Political Elites and their Point of View on Equal Gender Political Roles - TRAN, HUONG THI; THI LE, THUC (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT According to the article “Global Gender Gap Report 2020” of the World Economic Forum, on gender equality ranking roles by country, women’s political participation in Vietnam has dropped ten places, from 77th in 2018 to 87th in 2019. Research results show that the majority of respondents believe both genders should play equal political roles in the country, although certain differences were observed in the attitudes of different groups of respondents on gender, age, and education level. These sub-groups also demonstrate certain notable trends when discussing measures to promote women’s political participation in Vietnam. RESUMEN Según el artículo "Global Gender Gap Report 2020" del Foro Económico Mundial, sobre los roles de clasificación de la igualdad de género por país, la participación política de las mujeres en Vietnam ha caído diez lugares, del 77 en 2018 al 87 en 2019. Los resultados de la investigación muestran que la mayoría de los encuestados cree que ambos géneros deberían desempeñar papeles políticos iguales en el país, aunque se observaron ciertas diferencias en las actitudes de los diferentes grupos de encuestados sobre género, edad y nivel educativo. Estos subgrupos también demuestran ciertas tendencias notables cuando se discuten las medidas para promover la participación política de la mujer en Vietnam.